The Digestive Tract of Cephalopods: a Neglected Topic of Relevance to Animal Welfare in the Laboratory and Aquaculture - Sykes, António V.; Almansa, Eduardo; Cooke, Gavan M.; Ponte, Giovanna; Andrews, Paul L. R. (Frontiers in Physiology, 2017)
Maintenance of health and welfare of a cephalopod is essential whether it is in a research, aquaculture or public display. The inclusion of cephalopods in the European Union legislation (Directive 2010/63/EU) regulating the use of animals for scientific purposes has prompted detailed consideration and review of all aspects of the care and welfare of cephalopods in the laboratory but the information generated will be of utility in other settings. We overview a wide range of topics of relevance to the cephalopod digestive tract physiology and their relationship to the health and welfare of these animals. Major topics reviewed include: i) Feeding cephalopods in captivity which deals with live food and prepared diets, feeding frequency (ad libitum vs intermittent) and the amount of food provided; ii) The particular challenges in feeding hatchlings and paralarvae, as feeding and survival of paralarvae remain major bottlenecks for the aquaculture of e.g. Octopus vulgaris; iii) Digestive tract parasites and ingested toxins are discussed not only from the perspective of the impact on digestive function and welfare but also as potential confounding factors in research studies; iv) Food deprivation is sometimes necessary (e.g. prior to anaesthesia and surgery, to investigate metabolic control) but what is the impact on a cephalopod, how can it be assessed and how does the duration relate to regulatory threshold and severity assessment? Reduced food intake is also reviewed in the context of setting humane end-points in experimental procedures; v) A range of experimental procedures are reviewed for their potential impact on digestive tract function and welfare including anaesthesia and surgery, pain and stress, drug administration and induced developmental abnormalities. The review concludes by making some specific recommendations regarding reporting of feeding data and identifies a number of areas for further investigation. The answer to many of the questions raised here will rely on studies of the physiology of the digestive tract.